Soluble microneedle as well as raw materials, preparation method and application thereof

Through the specific preparation methods and treatment techniques of crosslinked hyaluronic acid, the problems of crosslinked hyaluronic acid microneedles being quickly degraded in the body and the generation of bubbles during the preparation process are solved, and the needle tip has been fully morphologically, excellent mechanical properties and transdermal effect are achieved. Ideal soluble microneedle meets the time and safety requirements of degradation in vivo.

CN119215180APending Publication Date: 2024-12-31MEIYAN SPACE (HEBEI) BIOTECHNOLOGY CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411370012.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing crosslinked hyaluronic acid microneedles have fast degradation speed in the body, short retention time, poor transdermal performance, and are prone to bubbles during the preparation process, incomplete needle tips, poor mechanical properties, and easy to break.

Method used

The crosslinked hyaluronic acid is used as the raw material, and the proportional control of specific crosslinking agents and preparation methods, including alkaline substances, crosslinking agents and solvents, are carried out first crosslinking and secondary crosslinking, combined with homogenization and centrifugation treatment. Exclude bubbles and improve needle tip morphological integrity and mechanical properties.

Benefits of technology

The resulting soluble microneedle needle tip has complete shape, excellent mechanical properties, ideal transdermal effect, not easy to break, meets the needs during degradation in the body, and has high safety in use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215180A_ABST
    Figure CN119215180A_ABST
Patent Text Reader

Abstract

The invention discloses a soluble microneedle as well as raw materials, a preparation method and application thereof. The raw material of the soluble microneedle comprises cross-linked hyaluronic acid, and the cross-linked hyaluronic acid is prepared by cross-linking hyaluronic acid substances with the average weight-average molecular weight of 60 WDa to 80 WDa. Specific cross-linked hyaluronic acid is adopted as a raw material to prepare the soluble microneedle, and pretreatment of homogenization and centrifugation is performed before film injection, so that bubbles in a system can be effectively eliminated, the needle tip of the prepared soluble microneedle is enabled to be regular in morphology, and meanwhile, the prepared soluble microneedle is excellent in mechanical property, ideal in transdermal effect and not easy to break, and has a good application prospect. The in-vivo degradation time meets the requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical technology, and in particular to a soluble microneedle, and raw materials, a preparation method and application thereof. Background Art

[0002] Dissolving microneedles refer to micro needles made of a material with certain mechanical properties, with a length between 25 and 2000 μm, a base diameter between 50 and 300 μm, and a tip diameter between 1 and 30 μm. The needles are regularly arranged on patches of different sizes, which is currently an effective, convenient, and well-tolerated transdermal drug delivery method. In the field of medical beauty, soluble microneedles are mainly local patch products with effects such as anti-wrinkle, whitening, and acne removal, such as anti-wrinkle eye patches and acne patches. Compared with other types of microneedles, soluble microneedles can carry more types of drugs. The microneedles penetrate the subcutaneous part without touching the skin's pain nerve endings, and will not cause pain when used. They will only form micron-sized wounds on the skin surface, which can heal within 24 to 48 hours. The treatment method is gentler and safer.

[0003] Hyaluronic acid (HA), carboxymethyl cellulose, chondroitin sulfate, polyvinyl alcohol, polyvinyl pyrrolidone, polylactide, chitosan, etc. can all be used as materials for preparing soluble microneedles. Among them, HA has strong drug loading capacity and biodegradability. HA can also play a unique role in protecting the skin, keeping the skin moisturized, smooth, delicate, tender and elastic, and also has the effects of anti-wrinkle, anti-wrinkle, beauty care and restoring skin physiological functions. However, HA will be rapidly degraded by the enzymatic hydrolysis of hyaluronidase in the body, has a short retention time in the body, the needle tip is easy to bend, and the transdermal effect is poor. Cross-linked hyaluronic acid is a polymer gel with a three-dimensional structure obtained by cross-linking and modifying HA with a cross-linking agent. Cross-linked hyaluronic acid microneedles can not only improve the retention time in the body, but also provide filling effect and skin care effect. However, the current cross-linked hyaluronic acid microneedles are prone to poor raw material fluidity, bubble generation, incomplete microneedle tips, poor mechanical properties of the prepared microneedles and easy breakage during the preparation process.

[0004] Therefore, there is an urgent need in this field to develop a soluble microneedle with a simple preparation process, low cross-linking agent residue, high safety of use, few bubbles in the microneedles, complete microneedle tip morphology, ideal mechanical properties and transdermal effects, and a degradation time in the body that meets actual needs and has ideal use value. Summary of the invention

[0005] The technical problem to be solved by the present application is to overcome the defects of the non-cross-linked hyaluronic acid microneedles in the prior art, such as fast degradation speed in vivo, short residence time, poor transdermal performance and easy bending; and the defects of the existing cross-linked hyaluronic acid microneedles in the preparation process, such as poor gel fluidity, easy generation of bubbles, incomplete microneedle tips, poor mechanical properties of the prepared microneedles, easy breakage, etc., and provide a soluble microneedle, and its raw materials, preparation method and application. The soluble microneedle tips prepared in the present application are complete in shape, have ideal mechanical properties and transdermal effects, and the degradation time in vivo meets the use requirements, and the use safety is high.

[0006] This application solves the above technical problems through the following technical solutions.

[0007] The present application provides a soluble microneedle raw material, including cross-linked hyaluronic acid, wherein the cross-linked hyaluronic acid is prepared by cross-linking a hyaluronic acid substance having an average weight-average molecular weight of 60 WDa to 80 WDa.

[0008] In some embodiments, the preparation method of the cross-linked hyaluronic acid includes the following steps: the cross-linking solution includes an alkaline substance, a cross-linking agent and a solvent; the hyaluronic acid substance with an average weight-average molecular weight of 60WDa to 80WDa is mixed with the cross-linking solution, and the cross-linked hyaluronic acid is obtained by cross-linking.

[0009] In the preparation process of the cross-linked hyaluronic acid, the alkaline substance is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate.

[0010] During the preparation of the cross-linked hyaluronic acid, the mass ratio of the alkaline substance to the solvent is (0.008-0.012):1, for example, 0.01:1.

[0011] In the preparation process of the cross-linked hyaluronic acid, the cross-linking agent is a cross-linking agent containing at least two epoxy groups, preferably selected from at least one of 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether and poly(dimethylsiloxane) diglycidyl ether.

[0012] During the preparation of the cross-linked hyaluronic acid, the volume mass ratio of the cross-linking agent to the hyaluronic acid-based substance is 100 to 300 μL / g, preferably 160 to 240 μL / g, for example 200 μL / g.

[0013] In the preparation process of the cross-linked hyaluronic acid, the solvent is water, preferably selected from at least one of deionized water, distilled water, purified water and water for injection.

[0014] In the preparation process of the cross-linked hyaluronic acid, the hyaluronic acid-like substance is selected from hyaluronic acid and / or hyaluronate. Preferably, the hyaluronate is selected from at least one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate and zinc hyaluronate.

[0015] During the preparation of the cross-linked hyaluronic acid, the average weight-average molecular weight of the hyaluronic acid-based substance is 65WDa to 80WDa, for example, 60WDa, 62WDa, 64WDa, 66WDa, 68WDa, 70WDa, 72WDa, 74WDa, 76WDa, 78WDa or 80WDa.

[0016] During the preparation of the cross-linked hyaluronic acid, the mass volume ratio of the hyaluronic acid substance to the solvent is 0.05-0.2 g / mL, for example, 0.06 g / mL, 0.08 g / mL, 0.1 g / mL, 0.12 g / mL, 0.14 g / mL, 0.16 g / mL, 0.18 g / mL or 0.2 g / mL.

[0017] In the preparation process of the cross-linked hyaluronic acid, the cross-linking includes primary cross-linking and secondary cross-linking; wherein the temperature of the primary cross-linking is 35-45°C; and the temperature of the secondary cross-linking is 15-30°C.

[0018] Preferably, the primary cross-linking temperature is 38-42°C, for example 40°C.

[0019] Preferably, the time of the primary cross-linking is 2 to 6 hours, for example 4 hours.

[0020] Preferably, the secondary cross-linking time is 24 to 48 hours.

[0021] During the preparation of the cross-linked hyaluronic acid, the cross-linking operation may further include at least one of adjusting the pH value of the system to neutral, washing and drying.

[0022] When the pH value of the regulating system is adjusted to neutral, the pH regulator is an acidic pH regulator, preferably hydrochloric acid. Preferably, the concentration of hydrogen chloride in the hydrochloric acid is 0.05-0.5 mol / L, for example 0.1 mol / L.

[0023] Wherein, the cleaning agent used for cleaning is selected from salt solution and / or water.

[0024] Preferably, the salt solution is a phosphate buffer. More preferably, the phosphate buffer comprises KH2PO4, NaCl, Na2HPO4, KCl and water; further preferably, the phosphate buffer comprises 1.5-2.5mM KH2PO4, 125-145mM NaCl, 8-12mM Na2HPO4, 2-3.5mM KCl and water; for example, it comprises 2.0mM KH2PO4, 137mM NaCl, 10.0mM Na2HPO4, 2.7mM KCl and water.

[0025] Preferably, the osmotic pressure of the salt solution is 275-305 mOsm / L, for example 300 mOsm / L.

[0026] Preferably, the pH value of the salt solution is 7.0-7.5, for example 7.4.

[0027] Wherein, the cleaning time is 1 to 4 hours, for example 2 hours.

[0028] The drying may be freeze-drying conventionally used in the art.

[0029] In some embodiments, the soluble microneedle raw material further comprises hyaluronic acid and / or active factors. According to the conventional understanding of those skilled in the art, the hyaluronic acid is a non-cross-linked hyaluronic acid added to the soluble microneedle raw material in addition to the cross-linked hyaluronic acid.

[0030] Wherein, the hyaluronic acid substance is selected from hyaluronic acid and / or hyaluronate.

[0031] Preferably, the hyaluronate is selected from at least one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate and zinc hyaluronate.

[0032] Wherein, the average weight average molecular weight of the hyaluronic acid substance is 60WDa-80WDa.

[0033] The mass ratio of the dry weight of the cross-linked hyaluronic acid to the hyaluronic acid-like substance is 1: (0.5-4), preferably 1: (0.5-2), for example 1: 1. The dry weight is the constant weight of the cross-linked hyaluronic acid after drying, that is, the weight after water loss, as conventionally considered by those skilled in the art. When the proportion of the cross-linked hyaluronic acid is too high, the fluidity of the injection molding material will be poor, and injection and needle making will be more difficult.

[0034] Wherein, the active factors include active factors with cosmetic effects, preferably selected from at least one of vitamins, epidermal growth factors and skin moisturizers.

[0035] The present application also provides a method for preparing a soluble microneedle, wherein the raw material is the soluble microneedle raw material as described above, and the method specifically comprises the following steps:

[0036] (1) The soluble microneedle raw material is mixed with water, homogenized, and centrifuged to obtain material A;

[0037] (2) Injecting the material A into the microneedle mold, removing bubbles, and drying.

[0038] In step (1), the water is selected from at least one of deionized water, distilled water, purified water and water for injection.

[0039] In step (1), the mass volume ratio of the dry weight of the cross-linked hyaluronic acid in the soluble microneedle raw material to the water is 5 to 20 mg / mL, for example, 10 mg / mL.

[0040] In step (1), the homogenization can be performed in a homogenizer according to the conventional practice in the art.

[0041] In step (1), the homogenizing speed is 4000-8000 rpm, for example, 5000 rpm.

[0042] In step (1), the homogenization time is 5 to 20 minutes, for example, 10 minutes.

[0043] In step (1), the centrifugal speed is 8000-12000 rpm, for example, 10000 rpm. When the centrifugal speed is lower than 8000 rpm, the defoaming effect is not ideal, which eventually results in bubbles in the prepared soluble microneedles and incomplete needle tip shape.

[0044] In step (1), the centrifugation time is 5 to 20 minutes, for example, 10 minutes.

[0045] In step (2), the method for removing bubbles is selected from decompression and / or suction.

[0046] The decompression can be carried out by using a vacuum pump according to the conventional method in the art.

[0047] Wherein, the vacuum degree of the system during the decompression is 0.08-0.09 MPa.

[0048] Wherein, the decompression time is 4 to 8 minutes. When the decompression time is less than 4 minutes, the defoaming effect is not ideal, resulting in bubbles in the soluble microneedle and an incomplete needle tip shape. When the decompression time is more than 8 minutes, the needle tip of the soluble microneedle is brittle and easy to break during use, resulting in poor transdermal effect.

[0049] The aspiration can be performed by using a pipette as is conventional in the art.

[0050] In step (2), the number of times of removing bubbles can be 2 to 3 times.

[0051] In step (2), the drying can be performed in an oven according to the conventional practice in the art.

[0052] In step (2), the drying temperature is 32-40°C, preferably 35-37°C.

[0053] In step (2), the injection, the removal of bubbles and the drying operations can be performed cyclically. That is, according to the conventional art, the material A can be added in multiple times, and the removal of bubbles and the drying operations are performed after each injection.

[0054] Wherein, during the circulation process, the drying time before the injection is 1 to 6 hours, preferably 2 to 4 hours.

[0055] The last drying time is 10 to 20 hours, for example 12 hours.

[0056] In step (2), the drying operation may be followed by a demoulding operation.

[0057] The present application also provides a soluble microneedle, which is prepared by the preparation method of the soluble microneedle as described above.

[0058] On the basis of conforming to the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present application.

[0059] The reagents and raw materials used in this application are commercially available.

[0060] The positive progress of the present application is that the present application adopts specific cross-linked hyaluronic acid as the raw material to prepare soluble microneedles, and performs homogenization and centrifugation pretreatment before injection, which can effectively remove bubbles in the system and make the needle tip morphology of the prepared soluble microneedles regular. At the same time, the prepared soluble microneedles have excellent mechanical properties, ideal transdermal effect, are not easy to break, and the degradation time in the body meets the requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a comparison graph of the degradation rate of cross-linked hyaluronic acid obtained in Experimental Example 1 in the presence of hyaluronidase or PBS buffer over time;

[0062] Figure 2 It is the standard curve diagram of BDDE content and absorbance value;

[0063] Figure 3 This is a graph showing the changes in cell survival rate under different concentrations and culture time conditions of sodium hyaluronate in the soluble microneedle raw material of Example 1;

[0064] Figure 4This is a graph showing the changes in cell survival rate of the cross-linked hyaluronic acid in the soluble microneedle raw material in Example 1 under different concentrations and culture time conditions;

[0065] Figure 5 This is a test diagram of the mechanical properties of the soluble microneedles prepared in Example 1, and three groups were tested in parallel;

[0066] Figure 6 The pictures are taken after rat skin was punctured with the soluble microneedles prepared in Example 1 and after trypan blue staining;

[0067] Figure 7 This is a picture taken after rat skin was pricked with the soluble microneedles prepared in Comparative Example 1;

[0068] Figure 8 This is a macroscopic photograph of the soluble microneedles prepared in Example 1;

[0069] Fig. 9 Optical microscope image of the soluble microneedles prepared in Example 1;

[0070] Fig.10 SEM image of the soluble microneedles prepared in Example 1;

[0071] Fig.11 Comparative Example 1 shows a macroscopic photograph of the soluble microneedles prepared;

[0072] Fig.12 Optical microscope image of the soluble microneedles prepared in Comparative Example 1. DETAILED DESCRIPTION

[0073] The present application is further described below by way of examples, but the present application is not limited to the scope of the examples. The experimental methods without specific conditions in the following examples are selected according to conventional methods and conditions, or according to the product instructions.

[0074] The reagents and raw materials used in the following examples are all commercially available, and the purity of the reagents used is injection grade.

[0075] In the following test examples and embodiments, sodium hyaluronate A was purchased from Bloomage Biotechnology with a product number of 18061301 and an average weight-average molecular weight of 78 WDa.

[0076] In the following test examples and embodiments, sodium hyaluronate B was purchased from McLean with a product number of C16205887. The average weight average molecular weight of the sodium hyaluronate tested by GPC was 4 WDa.

[0077] In the following test examples and embodiments, sodium hyaluronate C was purchased from McLean with a product number of C15067541. The average weight average molecular weight of the sodium hyaluronate tested by GPC was 10 WDa.

[0078] In the following test examples and embodiments, sodium hyaluronate D was purchased from McLean with a product number of C15124271. The average weight average molecular weight of the sodium hyaluronate tested by GPC was 120 WDa.

[0079] In the following test example, the PBS buffer includes 2.0 mM KH2PO4, 137 mM NaCl, 10.0 mM Na2HPO4, and 2.7 mM KCl; the osmotic pressure of the PBS buffer after preparation is 300 mOsm / kg, and the pH value is 7.4.

[0080] Experimental Example 1 Preparation of cross-linked hyaluronic acid

[0081] 100 mg of NaOH was dissolved in 10 g of distilled water to prepare a sodium hydroxide aqueous solution, followed by adding 200 μL of BDDE, stirring magnetically for 5 min, and mixing evenly to obtain a cross-linked solution. 1 g of sodium hyaluronate A with an average weight-average molecular weight of 78 WDa was added to the cross-linking solvent, stirred evenly in a 40°C water bath, cross-linked for 4 h, and then placed at room temperature for 1 day to obtain a gel. After the reaction was completed, the gel was soaked in distilled water, the pH value of the system was adjusted to neutral with 0.1 mol / L HCl, and then purified with PBS buffer (osmotic pressure of 300 mOsm / kg, pH value of 7.4) for 2 h, and then washed with distilled water for 1 day under stirring at room temperature, and the water was changed four times during the period to remove unreacted BDDE, sodium hyaluronate A and residual salt to obtain cross-linked hyaluronic acid.

[0082] The cross-linked hyaluronic acid was placed in a vacuum drying dish and stored at -80°C overnight, and then freeze-dried in a freeze dryer for 36 hours to obtain a cross-linked hyaluronic acid solid.

[0083] Test Examples 2 to 4

[0084] Compared with Experimental Example 1, the only difference is the average weight-average molecular weight of sodium hyaluronate. Other conditions and parameters are the same as those in Experimental Example 1. Cross-linked hyaluronic acid and cross-linked hyaluronic acid solid are prepared. For details, please see Table 1 below.

[0085] Table 1

[0086] Raw material sodium hyaluronate type Average weight average molecular weight of sodium hyaluronate Test Example 2 Sodium Hyaluronate B 4WD Test Example 3 Sodium Hyaluronate C 10WDa Test Example 4 Sodium Hyaluronate D 120WDa

[0087] Example 1 Preparation of soluble microneedles

[0088] (1) 30 mg of sodium hyaluronate (average weight average molecular weight of 78 WDa) and 3 mL of water were mixed to prepare a sodium hyaluronate aqueous solution with a concentration of 10 mg / mL. After complete dissolution, 30 mg of the cross-linked hyaluronic acid solid prepared in the above-mentioned Experimental Example 1 was weighed and added to the sodium hyaluronate aqueous solution. The mixture was evenly mixed and homogenized in a homogenizer for 10 min at a speed of 5000 rpm. The homogenized material was transferred to a centrifuge and centrifuged at 10000 rpm for 10 min to obtain a soluble microneedle raw material, which was stored in a refrigerator at 4°C for later use;

[0089] (2) Add the soluble microneedle raw material obtained in step (1) into the mold with a pipette, evacuate with a vacuum pump, the vacuum degree is 0.08 MPa, the decompression time is 6 min, and remove excess bubbles with a pipette, repeat three times; place in a 37°C oven and bake for 2 to 3 h; cycle the above operation, i.e. continue to add sample, decompress with a pipette to remove bubbles and dry until the addition is completed, and dry for the last time in a 37°C oven for 12 h, and demold after drying to obtain soluble microneedles.

[0090] Comparative Example 1 (Compared with Example 1, the difference is that sodium hyaluronate with an average weight average molecular weight of 120 WDa and the cross-linked hyaluronic acid solid prepared in Test Example 4 are used)

[0091] (1) 30 mg of sodium hyaluronate (average weight average molecular weight of 120 WDa) and 3 mL of water were mixed to prepare a sodium hyaluronate aqueous solution with a concentration of 10 mg / mL. After complete dissolution, 30 mg of the cross-linked hyaluronic acid solid prepared in the above-mentioned Experimental Example 4 was weighed and added to the sodium hyaluronate aqueous solution. The mixture was evenly mixed and homogenized in a homogenizer for 10 min at a speed of 5000 rpm. The homogenized material was transferred to a centrifuge and centrifuged at 10000 rpm for 10 min to obtain a soluble microneedle raw material, which was stored in a refrigerator at 4°C for later use;

[0092] (2) Add the soluble microneedle raw material obtained in step (1) into the mold with a pipette, evacuate with a vacuum pump, the vacuum degree is 0.08 MPa, the decompression time is 6 min, and remove excess bubbles with a pipette, repeat three times; place in a 37°C oven and bake for 2 to 3 h; cycle the above operation, i.e. continue to add sample, decompress with a pipette to remove bubbles and dry until the addition is completed, and dry for the last time in a 37°C oven for 12 h, and demold after drying to obtain soluble microneedles.

[0093] Comparative Example 2 (Compared with Example 1, the difference is that the soluble microneedle raw material is not centrifuged)

[0094] (1) 30 mg of sodium hyaluronate (average weight average molecular weight of 78 WDa) and 3 mL of water were mixed to prepare a sodium hyaluronate aqueous solution with a concentration of 10 mg / mL. After it was completely dissolved, 30 mg of the cross-linked hyaluronic acid solid prepared in the above-mentioned Experimental Example 1 was weighed and added to the sodium hyaluronate aqueous solution. The mixture was mixed evenly and homogenized in a homogenizer for 10 min at a homogenization speed of 5000 rpm to obtain a soluble microneedle raw material, which was stored in a refrigerator at 4°C.

[0095] (2) Add the soluble microneedle raw material obtained in step (1) into the mold with a pipette, evacuate with a vacuum pump, the vacuum degree is 0.08 MPa, the decompression time is 6 min, and remove excess bubbles with a pipette, repeat three times; place in a 37°C oven and bake for 2 to 3 h; cycle the above operation, i.e. continue to add sample, decompress with a pipette to remove bubbles and dry until the addition is completed, and dry for the last time in a 37°C oven for 12 h, and demold after drying to obtain soluble microneedles.

[0096] Comparative Example 3 (Compared with Example 1, the difference is that sodium hyaluronate with an average weight average molecular weight of 10 WDa and the cross-linked hyaluronic acid solid prepared in Test Example 3 are used)

[0097] (1) 30 mg of sodium hyaluronate (average weight average molecular weight of 10 WDa) and 3 mL of water were mixed to prepare a sodium hyaluronate aqueous solution with a concentration of 10 mg / mL. After complete dissolution, 30 mg of the cross-linked hyaluronic acid solid prepared in the above-mentioned Experimental Example 3 was weighed and added to the sodium hyaluronate aqueous solution. The mixture was evenly mixed and homogenized in a homogenizer for 10 min at a speed of 5000 rpm. The homogenized material was transferred to a centrifuge and centrifuged at 10000 rpm for 10 min to obtain a soluble microneedle raw material, which was stored in a refrigerator at 4°C for later use;

[0098] (2) Add the soluble microneedle raw material obtained in step (1) into the mold with a pipette, and evacuate with a vacuum pump to a vacuum degree of 0.08 MPa, and the decompression time is 6 min. Use a pipette to suck out excess bubbles, and repeat three times; place in a 37°C oven and bake for 2 to 3 h; cycle the above operation, i.e. continue to add sample, decompress with a pipette to remove bubbles and dry until the addition is completed, and dry for the last time in a 37°C oven for 12 h, and demold after drying.

[0099] The raw material obtained in step (1) has high viscosity, so it is difficult to inject the soluble microneedle raw material into the mold in step (2), and the needle tip shape of the obtained soluble microneedle is incomplete.

[0100] Effect Example 1

[0101] The properties of the cross-linked hyaluronic acid obtained in the above-mentioned test examples 1 to 3 were observed, and the rheological properties were tested using the lamina measuring system of a rheometer (HAAKE MARS60). The test temperature was set to 25° C., the frequency range was 0.1 to 10 Hz, and the elastic modulus (G') and complex viscosity (η) were read at a frequency of 1 Hz. The results are shown in Table 2.

[0102] Table 2

[0103] Elastic modulus (G') Complex viscosity (η) Characteristics Test Example 1 550Pa 13Pa·s gel Test Example 2 / / Non-gel

[0104] The results showed that in Experimental Example 2, cross-linked hyaluronic acid could not be prepared due to the low weight average molecular weight of the raw material sodium hyaluronate B.

[0105] Effect Example 2 Swelling Rate Characterization

[0106] A certain mass of the cross-linked hyaluronic acid solid prepared in the above-mentioned Experimental Example 1 was weighed and dissolved in deionized water at 37° C. until swelling equilibrium was reached. The hydrogel was then taken out and the excess water on the surface was removed with filter paper and weighed.

[0107] The equilibrium swelling ratio (S) was calculated based on the following equation: R ): S R =(W S -W0) / W0

[0108] W S and W0 are the masses of swollen hydrogel and weighed cross-linked hyaluronic acid solid, respectively. All experiments were performed three times.

[0109] The swelling rates obtained in three experiments were 70.5%, 61.3%, and 53.6% respectively; the average swelling rate was 61.8%.

[0110] Effect Example 3 Enzyme Degradation Performance of Cross-linked Hyaluronic Acid

[0111] The cross-linked hyaluronic acid solid prepared in the above-mentioned test example 1 was added to a PBS solution for swelling, and the gel sample after reaching equilibrium was weighed (W0), and further immersed in a PBS solution containing 45 U / mL hyaluronidase (HAase) at 37°C. Excess PBS was gently removed at regular intervals, and the sample was weighed (W t ). Fresh hyaluronidase solution was added after each measurement to ensure constant enzyme activity over time.

[0112] The degree of enzyme degradation is expressed as: Sample residual rate (%) = (W t / W0)×100%

[0113] The cross-linked hyaluronic acid prepared in the above-mentioned Experimental Example 1 was taken, and the experimental group (two groups were set up in parallel, named Gel1 and Gel2, respectively) was added with hyaluronidase solution, and the blank control group (named Gel3) was added with an equal amount of PBS solution.

[0114] The results are as follows Figure 1 As shown, after immersing cross-linked hyaluronic acid in hyaluronidase solution, the average residual rate of the experimental group was about 52.5% after 15 hours, while the residual rate of the blank control group was about 88.3% after 15 hours. After 30 hours, the average residual rate of the experimental group was about 20%, while the residual rate of the blank control group was about 80% after 30 hours. This shows that in the presence of hyaluronidase, cross-linked hyaluronic acid can be slowly degraded in the body, achieving a sustained release effect.

[0115] Effect Example 4 Determination of BDDE Residues

[0116] Fluorescence spectrophotometry was used to determine the residual amount of BDDE in the cross-linked hyaluronic acid prepared in Experimental Example 1. BDDE reacts with nicotinamide, and its fluorescence intensity is proportional to the amount of BDDE. A standard curve (such as Figure 2 As shown), the standard curve is y=1.87811x+0.13101, R 2 =0.99953.

[0117] The residual BDDE rate in the cross-linked hyaluronic acid prepared in Test Example 1 was 0.69 μg / mL. In 1 mL of the preparation, BDDE below 2 μg is harmless to the human body, indicating that the sample prepared by the cross-linked hyaluronic acid in Test Example 1 meets the safety requirements.

[0118] Effect Example 5 Biosafety Evaluation of Cross-linked Hyaluronic Acid and Non-cross-linked Sodium Hyaluronate

[0119] The cells used were HaCat cells (human immortalized keratinocytes), purchased from Shanghai Saibaikang Biotechnology. Complete culture medium was prepared according to the ratio of DMEM culture medium to fetal bovine serum of 9:1. HaCat cells were cultured in a 5% CO2, 37°C constant temperature incubator.

[0120] The detection method used was: CCK-8 method, which detected the changes in cell viability when HaCat cells were co-cultured with samples for 24 hours and 48 hours respectively.

[0121] The samples added to the experimental group 1 were different concentrations of the test solution prepared by sodium hyaluronate in the soluble microneedle raw material of Example 1. The samples added to the experimental group 2 were different concentrations of the test solution prepared by cross-linked hyaluronic acid in the soluble microneedle raw material of Example 1. The sample added to the control group was an equal amount of PBS solution.

[0122] Take HaCat cells in the logarithmic growth phase, count the cells, and adjust the cell concentration to 8×10 3 / well inoculated into a 96-well plate. According to the above grouping, add the corresponding samples to be tested, and after treatment, culture them in a 5% CO2, 37°C constant temperature incubator for 24h and 48h. Remove the culture medium, wash each well three times with PBS, add 10% CCK-8 culture medium at 130μL / well, and culture in a 5% CO2, 37°C constant temperature incubator for 2h. Take 80μL from each well into a 96-well plate, and detect the absorbance value at 450nm with an enzyme reader.

[0123] Relative activity % = (OD value of experimental group - background OD value) / (OD value of control group - background OD value) × 100%;

[0124] Among them, the background OD value is the absorbance of only adding CCK-8 reagent and culture medium.

[0125] The relative activity values ​​were plotted, and the results of Experiment 1 (sodium hyaluronate) were as follows: Figure 3 As shown, the results of Experiment 2 (cross-linked hyaluronic acid) are as follows Figure 4 As shown: after treating cells with cross-linked hyaluronic acid and non-cross-linked sodium hyaluronate for 24h and 48h, the cell viability was relatively high. It can be concluded that the raw materials of cross-linked hyaluronic acid and non-cross-linked sodium hyaluronate for preparing soluble microneedles in Example 1 are non-toxic to the human body, and the soluble microneedles prepared in Example 1 are highly safe to use.

[0126] Effect Example 6 Mechanical Properties Test

[0127] Soluble microneedles with sufficient mechanical strength can achieve the purpose of transdermal drug delivery. In order to better evaluate the ability of soluble microneedles to pierce the skin, the mechanical properties of the soluble microneedles prepared in Example 1 were tested using an electronic universal material testing machine. The test was conducted three times. The results are shown in Table 1. Figure 5 The average mechanical property was calculated to be 0.58N / needle.

[0128] Studies have shown that the insertion force required for the soluble microneedles to enter the skin barrier is about 0.054 N / needle, and the soluble microneedles must have sufficient mechanical strength to penetrate the skin. It can be seen that the soluble microneedles prepared in Example 1 have ideal mechanical properties and transdermal properties.

[0129] Effect Example 7 Microneedle Transdermal Performance Test

[0130] The animal model used was SD rats, and an in vitro skin puncture test was performed to determine whether the soluble microneedles prepared in Example 1 and Comparative Example 1 above can achieve effective transdermal administration.

[0131] The experimental process is as follows Figure 6 and Figure 7 As shown:

[0132] (1) The soluble microneedles of Example 1 were pressed onto the shaved back of rats for 5-10 minutes, leaving clear pinholes ( Figure 6 A, 6B), and then the pinhole was stained with trypan blue reagent for 30 minutes to obtain the stained image ( Figure 6 C). The results showed that the prepared soluble microneedles can pierce the stratum corneum and achieve the purpose of transdermal drug delivery.

[0133] (2) The soluble microneedles of Comparative Example 1 were pressed onto the shaved back of the rat for 5-10 minutes, leaving the pinholes as shown in the figure. Figure 7 As shown, it can be seen that the transdermal effect is not ideal, mainly because the soluble microneedles prepared in Comparative Example 1 are brittle and easy to break during use.

[0134] Effect Example 8 Morphological Characterization

[0135] The morphology of the soluble microneedles prepared in Example 1 and Comparative Examples 1 to 3 was observed.

[0136] See Example 1 for macroscopic photos of soluble microneedles. Figure 8 , optical microscope images see Fig. 9 , scanning electron microscope images see Fig.10 It can be seen that the needle tip of the soluble microneedle prepared in Example 1 has a complete and regular shape without bubbles.

[0137] The macroscopic photograph of the soluble microneedle tip of Comparative Example 1 is shown in Fig.11 , optical microscope images are shown in Fig.12 It can be seen that the needle tip morphology of the soluble microneedle prepared in Comparative Example 1 is incomplete and irregular, which leads to poor transdermal effect.

[0138] The soluble microneedle tips prepared in Comparative Examples 2 and 3 contained many bubbles, and some of the needle tips were incomplete in shape, which resulted in unsatisfactory transdermal effects.

[0139] Finally, it should be noted that in this application, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or apparatus.

[0140] Although the present application has been disclosed above through the description of the specific embodiments of the present application, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present application within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed in the present application.

Claims

1. A soluble microneedle raw material, characterized in that: The cross-linked hyaluronic acid is prepared by cross-linking hyaluronic acid substances with an average weight average molecular weight of 60WDa to 80WDa.

2. The soluble microneedle raw material according to claim 1, characterized in that: The preparation method of the cross-linked hyaluronic acid comprises the following steps: the cross-linking solution comprises an alkaline substance, a cross-linking agent and a solvent; the hyaluronic acid substance having an average weight average molecular weight of 60WDa to 80WDa is mixed with the cross-linking solution, and the cross-linked hyaluronic acid is obtained by cross-linking.

3. The soluble microneedle raw material according to claim 2, characterized in that: The preparation method of the cross-linked hyaluronic acid satisfies at least one of the following conditions (1) to (9): (1) The alkaline substance is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate; (2) The mass ratio of the alkaline substance to the solvent is (0.008-0.012):1; (3) The crosslinking agent is a crosslinking agent containing at least two epoxy groups, preferably selected from at least one of 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether and poly(dimethylsiloxane) diglycidyl ether; (4) The volume mass ratio of the cross-linking agent to the hyaluronic acid substance is 100 to 300 μL / g, preferably 160 to 240 μL / g; (5) The solvent is water, preferably at least one selected from deionized water, distilled water, purified water and water for injection; (6) The hyaluronic acid substance is selected from hyaluronic acid and / or hyaluronate; preferably, the hyaluronate is selected from at least one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate and zinc hyaluronate; (7) The average weight average molecular weight of the hyaluronic acid substance is 65 WDa to 80 WDa; (8) The mass volume ratio of the hyaluronic acid substance to the solvent is 0.05 to 0.2 g / mL; (9) The crosslinking includes primary crosslinking and secondary crosslinking; wherein the temperature of the primary crosslinking is 35-45°C; the temperature of the secondary crosslinking is 15-30°C; preferably, the temperature of the primary crosslinking is 38-42°C; preferably, the time of the primary crosslinking is 2-6 hours; preferably, the time of the secondary crosslinking is 24-48 hours.

4. The soluble microneedle raw material according to claim 2, characterized in that: In the preparation process of the cross-linked hyaluronic acid, the cross-linking operation further includes at least one of adjusting the pH value of the system to neutral, washing and drying.

5. The soluble microneedle raw material according to claim 4, characterized in that: The preparation method of the cross-linked hyaluronic acid satisfies at least one of the following conditions (1) to (4): (1) When the pH value of the adjustment system is neutral, the pH adjuster is an acidic pH adjuster, preferably hydrochloric acid; more preferably, the concentration of hydrogen chloride in the hydrochloric acid is 0.05 to 0.5 mol / L; (2) The cleaning agent used for the cleaning is selected from a salt solution and / or water; preferably, the salt solution is a phosphate buffer; more preferably, the phosphate buffer comprises KH2PO4, NaCl, Na2HPO4, KCl and water; preferably, the osmotic pressure of the salt solution is 275-305mOsm / L; preferably, the pH value of the salt solution is 7.0-7.5; (3) The cleaning time is 1 to 4 hours; (4) The drying method is freeze drying.

6. The soluble microneedle raw material according to any one of claims 1 to 5, characterized in that: The soluble microneedle raw material also includes hyaluronic acid substances and / or active factors.

7. The soluble microneedle raw material according to claim 6, characterized in that: The soluble microneedle raw material satisfies at least one of the following conditions (1) to (4): (1) The hyaluronic acid substance is selected from hyaluronic acid and / or hyaluronate; preferably, the hyaluronate is selected from at least one of sodium hyaluronate, potassium hyaluronate, calcium hyaluronate and zinc hyaluronate; (2) The average weight average molecular weight of the hyaluronic acid substance is 60 WDa to 80 WDa; (3) The mass ratio of the dry weight of the cross-linked hyaluronic acid to the hyaluronic acid-like substance is 1:(0.5-4), preferably 1:(0.5-2); (4) The active factors include active factors with cosmetic effects, preferably selected from at least one of vitamins, epidermal growth factors and skin moisturizers.

8. A method for preparing soluble microneedles, characterized in that: The raw material is the soluble microneedle raw material as claimed in any one of claims 1 to 7, and the preparation method of the soluble microneedle comprises the following steps: (1) The soluble microneedle raw material is mixed with water, homogenized, and centrifuged to obtain material A; (2) Injecting the material A into the microneedle mold, removing bubbles, and drying.

9. The method for preparing soluble microneedles according to claim 8, characterized in that: The method for preparing the soluble microneedle satisfies at least one of the following conditions (A) to (K): (A) In step (1), the water is selected from at least one of deionized water, distilled water, purified water and water for injection; (B) In step (1), the mass volume ratio of the dry weight of the cross-linked hyaluronic acid in the soluble microneedle raw material to the water is 5 to 20 mg / mL; (C) In step (1), the homogenization speed is 4000-8000 rpm; (D) In ​​step (1), the homogenization time is 5 to 20 minutes; (E) In step (1), the centrifugal speed is 8000-12000 rpm; (F) In step (1), the centrifugation time is 5 to 20 minutes; (G) In step (2), the method for removing bubbles is selected from decompression and / or suction; preferably, the vacuum degree of the system during decompression is 0.08 to 0.09 MPa; preferably, the decompression time is 4 to 8 minutes; (H) In step (2), the number of times of removing bubbles is 2 to 3 times; (I) In step (2), the drying temperature is 32-40°C, preferably 35-37°C; (J) In step (2), the injection, the removal of bubbles and the drying are performed in a cycle; preferably, during the cycle, the drying time before the injection is 1 to 6 hours, more preferably 2 to 4 hours; preferably, the last drying time is 10 to 20 hours; (K) In step (2), the drying operation further includes a demoulding operation.

10. A soluble microneedle, characterized in that: The soluble microneedle is prepared by the preparation method of the soluble microneedle as claimed in claim 8 or 9.